Teaching Curiosity: An Essential Advertising Skill?. (May 2014) - Koranda, David; Sheehan, Kim Bartel
Several advertising industry professionals believe curiosity is an essential skill for the advertising business. In this paper, we describe how an advanced undergraduate class provides experiences that allow students to tap into multiple dimensions of curiosity. We question students at both the start and the end of the class to better understand if class exercises based on various curiosity models have changed how students view curiosity.